Influence of temperature gradient on diffracted X-ray spectrum in quartz crystal; IOP Conference Series: Materials Science and Engineering; Vol. 135 : Issues of Physics and Technology in Science, Industry and Medicine - Mkrtchan (Mkrtchyan) A. R. Alpik Rafaelovich; Potylitsyn A. P. Alexander Petrovich; Vukolov A. V. Artem Vladimirovich; Novokshonov A. I. Artem Igorevich; Gogolev A. S. Aleksey Sergeevich; Amiragyan R. V.; Movsisyan A. E. (2016, 2016)
Title screen